2014
DOI: 10.1016/j.socscimed.2014.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Changing policy and practice: Making sense of national guidelines for osteoarthritis

Abstract: Understanding uptake of complex interventions is an increasingly prominent area of research. The interplay of macro (such as changing health policy), meso (re-organisation of professional work) and micro (rationalisation of clinical care) factors upon uptake of complex interventions has rarely been explored. This study focuses on how English General Practitioners and practice nurses make sense of a complex intervention for the management of osteoarthritis, using the macro-meso-micro contextual approach and Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(73 citation statements)
references
References 24 publications
0
73
0
Order By: Relevance
“…The searches identified 1612 titles, leaving 1175 after de‐duplication. Four articles that were eligible for inclusion in the review (Cuperus et al, ; Morden et al, ; Morden, Jinks, Ong, Porcheret, & Dziedzic, ; Ong et al, ). The review process is demonstrated in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The searches identified 1612 titles, leaving 1175 after de‐duplication. Four articles that were eligible for inclusion in the review (Cuperus et al, ; Morden et al, ; Morden, Jinks, Ong, Porcheret, & Dziedzic, ; Ong et al, ). The review process is demonstrated in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…This seems to be reflected in the clinical management, as it appears that the nurses focused on the core treatments of information provision, encouraging weight management and physical activity. This finding was also reflected in the post intervention group interview with the nurses, a component of the qualitative work within the MOSAICS study [43, 44]. In a group interview the nurses described how they felt more confident dealing with patients who consulted with OA and were able to modify their relationship with OA patients, because they had the opportunity to play more of an active role in patient care [43].…”
Section: Discussionmentioning
confidence: 99%
“…In a group interview the nurses described how they felt more confident dealing with patients who consulted with OA and were able to modify their relationship with OA patients, because they had the opportunity to play more of an active role in patient care [43]. Ong et al [44] also reported that the nurses recognised that they had lacked skills and knowledge of OA previously, felt that the training had helped to up skill them in this regard, and left them feeling they could manage patients with OA better than previously, and boosted their professional standing. Despite the nurses being encouraged to use the OA guidebook as part of each consultation, its use dropped off considerably over the course of the four consultations This may be due to the nurses feeling more knowledgeable and confident as reflected in the findings from the group interview, clinical management and post-training questionnaire data, and therefore they felt less reliant on the use of the written information.…”
Section: Discussionmentioning
confidence: 99%
“…178 Factors relevant to participation in the MOSAICS studies To facilitate recruitment and operationalisation of complex interventions, the research team needed to pay attention to the existing clinical concerns, internal power dynamics and workloads within individual primary care organisations. Logistics and existing communication channels influenced how health-care professionals made sense of the study and organised their roles in relation to it.…”
Section: Resultsmentioning
confidence: 99%